PELUANG PEMBELAJARAN BERBASIS TIK UNTUK PENGEMBANGAN DAN PENGAWASAN SISTEM BELAJAR TATAP MUKA - Etika Sabariah (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Advance technology information on globlatation very fast change. SDM must be user to up to date adaptation. The research see opportunity learning with ICT to development and carefuly system learning meeting with goals: 1) see opportunity use ICT to development and carefuly from system learning meeting,2) decrease risk copy paste to collection duty, 3) increase education honesty and competition to value evaluation. Method basicly to goals is basic researchwith analysis Cross Tabss and applied research with see fenomena. So timecross with mahasiswa from kind Univercity to event COMFEST X at UnivercityIndonesia. Kualitatif data with kuesioner. Deductif use correlation research and theory. Result research value chi square count 27,694<chi square table 28,870 to impact positive use ICT, and value chi square count 10,2848<chi square table 12,590 to impact negative use ICT. Its happening hipotesa Nul that the point out not there correlation from variable independent to dependent. The matter happening because sampling is mahasiswa from kinds university that not average implementation to reflection on the kuesioner. So applied research to catch fenomena and insipide problem solving by method: 1) repair design duty question, 2) use facility worksheets by application on computer, 3) collection task with use ICT. Keywords: Use ICT, Development, Carefully Learning.